High performance concrete applied in structural columns overlooking sustainability - Britez, C.; Pacheco, J.; Levy, S.; Helene, P. (Revista ALCONPAT, 2015)
In the last decades, the concept of sustainable construction has been addressed in several engineering projects in the world. The search of materials that provide more durable projects and with long service life is a worldwide consensus. Many researchers do not consider the concrete an attractive material from the standpoint of sustainable construction. This article aims to demystify this scenario and apply high performance concrete in structural columns aiming to sustainability issues. It is a case study of a building located in the municipality of São Paulo. It was noted that the concept of sustainable construction is absolutely in line with the use of high performance concrete in structural columns. Keywords: Sustainable construction, service life, concrete, high performance concrete.